Answer:
Step-by-step explanation:
Given the equation of motion;
S = ut + 1/2 at² where;
u is the initial velocity,
a is the acceleration, and;
t is the time.
We are to express a in terms of u, t and S
Making a the subject of the formula;
S = ut + 1/2 at²
S-ut = 1/2at²
2(S-ut) = at²
a = 2(S-ut)/t²
Hence the acceleration a in terms of other variables is expressed as a = 2(S-ut)/t²
Answer:
39420
Step-by-step explanation:
Multiply 2% by 365, then you get 7.3, multiply 7.3 by 3, then you get 21.9, then last step, multiply 21.9 by 1800$
Answer:
(2,6)
Step-by-step explanation:
Google
Answer:
63
Step-by-step explanation:
the answer is 63 because 6 to the power of 2 is 36 and 3 to the power of 3 is 27 add them together you get 63
Answer:
-2, -1, 0, 1, 2, 3, 4
Step-by-step explanation:
The number has to be smaller than 5 but greater than or equal to - 2